Book Review of How We Practice Therapy Now - Pasyk, Victoria S. (Canadian Journal of Counselling and Psychotherapy, 2023)
The practice of therapy is continuously evolving, but the global pandemic especially caused drastic and sudden shifts in our service delivery. Although therapists were generally able to adapt quickly, guidelines and suggestions for novel practices are lagging. This book was written to provide foundational knowledge on emergent practices as result of the pandemic and other influences. This essential read covers topics such as teletherapy, innovative approaches (such as concierge therapy) race/power, legal/ethical issues, and self-care. By reading this book, therapists will be able to strengthen their understanding on how we (should) practice therapy now.